2019
DOI: 10.1016/j.celrep.2019.05.099
|View full text |Cite
|
Sign up to set email alerts
|

A Role for FACT in RNA Polymerase II Promoter-Proximal Pausing

Abstract: Highlights d FACT regulates patterns of transcription-coupled histone marks d FACT knockdown reduces the half-life of promoterproximally paused Pol II d FACT helps to maintain promoter-proximal Pol II pausing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 62 publications
3
45
1
Order By: Relevance
“…Thus, the observed, low H3K36me3 signal indicates weak transcription elongation at genes with unstable Pol II, consistent with PRO-seq data. Conversely, genes with stable pausing exhibited stronger transcription activity and higher levels of H3K36me3 (Figures 1A and 1B), in agreement with recent work (Tettey et al, 2019).…”
Section: Resultssupporting
confidence: 92%
“…Thus, the observed, low H3K36me3 signal indicates weak transcription elongation at genes with unstable Pol II, consistent with PRO-seq data. Conversely, genes with stable pausing exhibited stronger transcription activity and higher levels of H3K36me3 (Figures 1A and 1B), in agreement with recent work (Tettey et al, 2019).…”
Section: Resultssupporting
confidence: 92%
“…The activation of MERVL-fused genes meant these genes need to switch from canonical promoters to MERVL-derived cryptic promoters (Figure 4E ). FACT interacts with RNA polymerase II (Figure 5A and Supplementary Table S5 ) and maintains RNA polymerase II pausing at the proximal promoter region ( 80 ), which prevents downstream cryptic transcription initiation ( 81 ). Besides MERVL, other TEs are capable to work as cryptic promoters to drive expression of oncogenes in human cancers ( 37 ), implying a potential role of FACT and other repressors of cryptic transcription in tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that the histone chaperones Spt6 and FACT (composed of Spt16 and Pob3) are also required for the normal distribution of several histone modifications, as shifts toward the 3′ end occurred in yeast spt6 and spt16 mutants ( 95 ), as well as after depletion of FACT in Drosophila cells ( 97 ). The yeast study suggested that these shifts were a consequence of transcription-dependent loss of histones on chromatin due to impaired nucleosome reassembly in the wake of transcription.…”
Section: Discussionmentioning
confidence: 99%